(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to reveal the effectiveness of a cognitive-behavioral therapeutic program in reducing social phobia disorder among a sample of patients attending psychiatric clinics in the Royal Medical Services, on a sample consisting of (30) individuals distributed into two equal groups: an experimental sample of (15) and a control sample of (15). 15) They were selected using the random sample method available during the year 2014, where the study population consisted of patients attending the Royal Medical Services Hospitals in general during the year 201, amounting to (100) patients.